A new energy vehicle high-conductivity aluminum material and a preparation method thereof

CN123027445APending Publication Date: 2026-11-03GUANGZHOU GOLDEN ALUMINUM ALUMINUM +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611481607.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies make it difficult to stably prepare high-conductivity pure aluminum materials on an industrial scale, and ECAP equipment is difficult to achieve continuous and large-scale production, which cannot meet the demand of new energy vehicles for large-volume, low-cost supply of conductive aluminum materials. At the same time, ECAP introduces a large number of grain boundaries and dislocations, making it difficult to stably achieve high conductivity levels.

Method used

By precisely adding boron through pre-furnace spectral analysis, combined with siphon slag removal and dual-stage filtration purification, and employing low-temperature refining and dual-stage annealing treatments, we ensure that impurity elements are converted into borides and reaction products are removed, thereby refining the grains and optimizing the microstructure to achieve a balance between high conductivity and mechanical properties.

Benefits of technology

We can stably produce high conductivity aluminum materials for new energy vehicles with a conductivity of over 64% IACS, significantly improving conductivity while maintaining strength, plasticity, and heat resistance. The process is highly controllable, with good performance consistency, meeting the high-end material requirements of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027445A_ABST
    Figure CN123027445A_ABST
Patent Text Reader

Abstract

The application discloses a new energy vehicle high-conductivity aluminum material and a preparation method thereof, and comprises the following steps: S1. pure aluminum is heated to 750-760 DEG C to be melted, and furnace front spectrum pre-analysis is carried out; according to the pre-analysis result, Al-3B is added, so that the total amount of boron element actually put into the furnace is 0.015-0.025%, sufficient stirring is carried out, and heat preservation is carried out; S2. the boride precipitate in the furnace bottom is sucked out and discarded by using siphon method, the upper clear liquid is taken, heat preservation is carried out for 30 min, the dross is regularly skimmed off, online degassing is carried out, double-stage filtration is carried out, natural cooling is carried out, a grain refiner is added, semi-continuous casting is carried out, and double-stage homogenizing annealing is carried out, so that the new energy vehicle high-conductivity aluminum material is obtained. The spectrum pre-analysis provides an accurate dose basis for boridation treatment, the siphon deslagging removes boridation reaction products for subsequent purification, low-temperature and low-dose refining provides uniform and small equiaxed crystal organization for ingot casting, the new energy vehicle high-conductivity aluminum material can be stably produced, the conductivity of the material is significantly improved, and the reliability requirement of high-end conductive materials in the new energy automobile field is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lightweight, highly conductive metal materials technology, specifically to a highly conductive aluminum material for new energy vehicles and its preparation method. Background Technology

[0002] With the global energy structure transformation and increasingly stringent environmental requirements, the new energy vehicle industry is developing rapidly, placing higher demands on vehicle lightweighting, improved driving range, and the efficient and stable operation of electrical systems. Among the lightweight, highly conductive metal materials used in new energy vehicles, aluminum and aluminum alloys are increasingly widely used in conductive components due to their advantages such as low density, good conductivity, and relatively low cost. Industrial pure aluminum 1070, with its high aluminum content (≥99.7%), possesses excellent conductivity and is one of the ideal materials for manufacturing high-voltage conductive components. However, traditional industrial pure aluminum casting processes typically achieve a conductivity of only around 61% IACS (International Annealed Copper Standard), which is insufficient to meet the urgent needs of new energy vehicles for lower line losses and higher energy transmission efficiency. Therefore, developing a production process capable of stably producing high conductivity (e.g., 63% IACS and above) industrial pure aluminum 1070 castings has become a key technological challenge and development direction in the upstream material preparation field of the current new energy vehicle industry chain, directly affecting the performance of downstream core components and the overall vehicle energy efficiency.

[0003] To improve the conductivity of industrial pure aluminum, existing technologies typically focus on two main aspects: raw material purity control and melt purification. Regarding raw material control, high-grade remelting aluminum ingots (such as Al99.70) are commonly used as the main raw material, with strict control over the upper limits of major impurity elements such as iron (Fe) and silicon (Si). For melt purification, conventional methods include: first, using a covering agent (such as a NaCl-KCl mixed salt) to cover the melt surface to reduce aluminum oxidation and gas absorption; second, introducing an inert gas (such as argon) or a chlorine mixture into the melt for rotary spray refining, removing hydrogen and inclusions through bubble adsorption; and third, using plate or tubular filter boxes with built-in ceramic filter plates to filter the aluminum melt, further removing solid inclusions. These methods can improve the purity of the aluminum melt to a certain extent, thereby improving conductivity. However, these conventional methods have obvious limitations: covering agents may introduce new impurities; gas refining has limited effectiveness in removing certain types of inclusions and extremely fine impurities, and improper control of process parameters (such as gas flow rate and time) can easily lead to secondary contamination of the melt or uneven composition; filtration is mainly for larger inclusions and has little effect on removing impurity elements that are dissolved in aluminum at the atomic scale, and these elements are the key factors affecting conductivity.

[0004] Factors affecting the electrical conductivity of aluminum include chemical composition, deformation, and dispersed second-phase particles, among which chemical composition is the most fundamental and decisive factor. The resistivity of aluminum increases as its purity decreases; the higher the impurity content, the higher the resistivity. Industrially pure aluminum contains various impurity elements, primarily Si, Fe, Ti, V, Mn, and Cr. Research by Zhang Qiang et al. (Foundry Technology, 2007, Vol. 28, No. 10, 1338-1340) shows that adding boron (B) to industrially pure aluminum effectively reduces the content of Ti and V, improving its electrical conductivity, but decreases tensile strength while significantly increasing elongation. Wang Guiqin's research (Study on the Influence of Boron on the Conductivity of Aluminum Conductors, Doctoral Dissertation, Dalian University of Technology, 2004) found that boron (B) can react with impurity elements Ti and Cr in aluminum, and also with Fe (but the reaction tendency is weaker than that of Ti and Cr), to form corresponding boron compounds. This transforms dissolved impurity elements in aluminum into precipitated borides, thereby improving the conductivity of aluminum conductors. Meanwhile, B has little effect on the strength and ductility of aluminum conductors. In recent years, adding trace amounts of boron to industrially pure aluminum for borylation has become a common technique for improving conductivity.

[0005] Chinese patent CN102978481B, "A Method for Preparing High-Strength, High-Conductivity Boron-Modified Industrial Pure Aluminum," discloses a method for producing high-strength, high-conductivity boron-modified industrial pure aluminum. The method involves melting industrial pure aluminum, adding an aluminum-boron master alloy to achieve a boron content of 0.02-0.2% in the molten aluminum, casting the ingot, and then subjecting the cast aluminum ingot to isochannel deformation (ECAP) to obtain high-strength, high-conductivity industrial pure aluminum. However, isochannel deformation requires specialized molds and equipment, making continuous, large-scale production difficult and unable to meet the demand of the new energy vehicle industry for large-volume, low-cost conductive aluminum materials. Furthermore, while ECAP can refine grains through intense plastic deformation, it introduces numerous grain boundaries and dislocations, negatively impacting conductivity and making it difficult for actual products to consistently achieve the claimed 65% IACS or higher conductivity.

[0006] Therefore, it is of great significance to develop a high conductivity aluminum material for new energy vehicles and its preparation method that can stably prepare high conductivity pure aluminum materials on an industrial scale and effectively control the borination reaction process and products. Summary of the Invention

[0007] Based on the aforementioned background technology, existing high-conductivity pure aluminum materials require ECAP-specific molds and equipment, making continuous and large-scale production difficult. This fails to meet the demand of the new energy vehicle industry for large-volume, low-cost conductive aluminum materials. Furthermore, while ECAP can refine grains through severe plastic deformation, it introduces numerous grain boundaries and dislocations, negatively impacting conductivity and making it difficult for actual products to consistently achieve high conductivity. Therefore, this invention provides a high-conductivity aluminum material for new energy vehicles and its preparation method. Pre-spectral analysis provides precise dosage information for boration treatment, siphon slag removal removes boration reaction products for subsequent purification, and online degassing and... Dual-stage filtration provides a high-purity melt environment for delayed refining, low-temperature and low-dose refining provides a uniform and fine equiaxed grain structure for the ingot, and dual-stage homogenization annealing releases the best conductivity and mechanical properties for the final product. It can stably produce high-conductivity aluminum materials for new energy vehicles with a conductivity of over 64% IACS, significantly improving the conductivity of the material and achieving an excellent balance between conductivity, strength, plasticity, and heat resistance. The production process is complete and highly controllable, and key process parameters can be precisely adjusted, ensuring batch stability and consistency of product performance. All performance indicators meet the reliability requirements of high-end conductive materials in the new energy vehicle field.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a high conductivity aluminum material for new energy vehicles includes the following steps: S1. Heat pure aluminum to 750-760℃ to melt it. Perform pre-furnace spectral analysis to determine the actual mass percentage of Ti, V, Cr, and Mn elements in the melt. Based on the pre-analysis results, add Al-3B to make the total mass percentage of boron elements actually entering the furnace 0.015-0.025 wt.%. Stir thoroughly and keep at 730-735℃ for 60-90 minutes. S2. The boron-containing precipitate at the bottom of the furnace is extracted and discarded by siphon method. The clear liquid at the top is kept at 715-725℃ for 30 minutes. The scum is skimmed off periodically, the gas is degassed online, filtered in two stages, and cooled naturally to 710-720℃. A grain refiner is added, and the mixture is semi-continuously cast and then homogenized in two stages to obtain the high conductivity aluminum material for new energy vehicles.

[0009] Preferably, the pure aluminum in S1 is 1070 industrial pure aluminum, with an aluminum content ≥99.7wt.%, Fe ≤0.15wt.%, and Si ≤0.08wt.%.

[0010] Preferably, the boron content in Al-3B in S1 is 2.5-3.5 wt.%.

[0011] Preferably, the amount of Al-3B added in S1 is calculated based on a molar ratio of boron to Ti+V+Cr+Mn of (1.2-1.5):1.

[0012] Preferably, the boron-containing precipitate in S2 accounts for 5-8 wt.% of the total mass of the molten aluminum.

[0013] Preferably, the operating temperature for extracting and discarding the boron-containing precipitate from the bottom of the furnace using the siphon method described in S2 is controlled at 720-735℃.

[0014] Preferably, after periodically skimming off the scum in step S2, the method further includes taking a sample of the supernatant for composition analysis to confirm that the residual boron content is ≤0.003wt.%.

[0015] Preferably, the grain refiner in S2 is Al-5Ti-0.8B-0.2C, and the addition amount is 0.10-0.18 wt.%.

[0016] In addition, the present invention also provides a high conductivity aluminum material for new energy vehicles.

[0017] A high conductivity aluminum material for new energy vehicles is prepared according to any one of the above preparation methods.

[0018] Preferably, by weight percentage, it comprises: Fe≤0.15wt.%, Si≤0.08wt.%, Cr+Mn+V+Ti≤0.01wt.%, Al≥99.75wt.%.

[0019] Preferably, the conductivity of the aluminum material is ≥64% IACS.

[0020] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a method for preparing high-conductivity aluminum materials for new energy vehicles. Through pre-furnace spectral analysis and dynamic boron addition, the amount of boron added is precisely matched with the impurity content, ensuring that Ti, V, Cr, and Mn are fully converted into boride precipitates while avoiding excessive boron residue. After the heat treatment and settling period and before the converter, a siphon is used to actively extract and discard the boride precipitate layer from the bottom of the furnace, physically removing the products of the borylation reaction and preventing secondary melting or resuspension of the boride in subsequent processes. Slag is periodically skimmed off, and gravity separation is further used to separate residual micro-inclusions and floating oxides, thus improving the purity of the melt. This second enhancement, combined with dynamic boron allocation, ensures that the conductivity improvement effect of boronizing treatment is retained to the greatest extent in the final product. This scheme positions the grain refiner feeder after the dual-stage filtration device and before the distribution channel. At this point, the molten aluminum has naturally cooled to 710-720℃, and the melt purity is optimal, which is conducive to the uniform dispersion of refiner particles and maximizes nucleation efficiency. The temperature is lower than the conventional refiner addition temperature, increasing the supercooling of the melt, causing the grain refiner particles to precipitate in a finer and more dispersed form, significantly improving nucleation efficiency. Only a low dosage is needed to achieve a uniform equiaxed grain structure of 50-70μm. This process avoids the negative impact of excessive Ti and B in high-dose refining agents on conductivity. The post-casting two-stage homogenization annealing process: the first stage promotes the precipitation of supersaturated solid solutions of impurities such as Fe and Si in the form of iron-containing phase compounds at grain boundaries, reducing electron scattering; the second stage promotes spheroidization and coarsening of the precipitated phases, eliminating as-cast segregation and micro-region compositional inhomogeneity. Simultaneously, it induces partial spheroidization of discontinuously distributed iron-containing phases at grain boundaries, reducing their adverse effects on plasticity. Combined with boronizing treatment, this forms a "dual-path purification," jointly reducing the amount of impurities dissolved in the aluminum matrix, resulting in a synergistic improvement in conductivity. Each step is interconnected and mutually reinforcing. The prerequisite is the ability to stably produce high-conductivity aluminum materials for new energy vehicles with a conductivity of over 64% IACS, significantly improving the material's conductivity and achieving an excellent balance between conductivity, strength, plasticity, and heat resistance. The production process is complete and highly controllable, with key process parameters that can be precisely adjusted, ensuring batch stability and consistency of product performance. The produced cast rods have a dense internal structure and fine grains, exhibiting excellent subsequent processing performance. All performance indicators meet the reliability requirements of high-end conductive materials in the new energy vehicle field, providing a high-quality raw material base for manufacturing high-performance wires and connectors. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a metallographic image of the high conductivity aluminum material for new energy vehicles prepared in Example 1 of the present invention.

[0023] Figure 2 This is a metallographic image of the high conductivity aluminum material for new energy vehicles prepared in Example 3 of the present invention. Detailed Implementation

[0024] To better illustrate the objectives, technical solutions, and advantages of this invention, the following embodiments are provided. Obviously, the following embodiments are only a part of the embodiments of this invention, and not all of them; these embodiments do not imply any limitation on this invention. Those skilled in the art should understand that these embodiments are only used to illustrate the technical effects of this invention, and not to limit the scope of protection of this invention.

[0025] Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. These examples are primarily intended to provide a better understanding of the analytical methods of this invention and do not exhaustively cover all possible procedures.

[0026] All raw materials used in the examples are commercially available; unless otherwise specified, the reagents, methods and equipment used in this invention are conventional reagents, methods and equipment in this technical field. Example 1

[0027] A method for preparing a high conductivity aluminum material for new energy vehicles includes the following steps: S1. Prepare 1070 aluminum ingots and clean waste materials according to the ratio of clean waste materials not exceeding 30% of the total feed amount. Select 1070 industrial pure aluminum ingots and clean waste materials with aluminum content ≥99.7wt.%, Fe≤0.15wt.%, and Si≤0.08wt.%. The waste materials are dried in a drying kiln at 250℃ for more than 2 hours to remove moisture and oil. The pure aluminum is heated to 754℃ to melt it. Perform pre-analysis of the spectrum before the furnace. Take the aluminum liquid in the furnace and use a direct reading spectrometer to quickly determine the actual mass percentage of Ti, V, Cr, and Mn elements in the melt. Calculate the molar ratio of boron to Ti+V+Cr+Mn elements as 1.5:1. According to the pre-analysis results, add Al-3B with a boron content of 3wt.% to make the total amount of boron elements actually fed into the furnace 0.021wt.%. Stir thoroughly and keep it at 732℃ for 65 minutes. S2. Under the condition of maintaining 730℃, the boron-containing precipitate, accounting for 5-8 wt.% of the total mass of aluminum liquid, is extracted and discarded from the bottom of the furnace using a siphon method. The upper clear liquid is transferred to a preheated holding furnace and held at 722℃ for 30 minutes. The scum is skimmed off periodically, and the upper clear liquid is sampled for composition analysis to confirm that the residual boron content is ≤0.003 wt.%. The aluminum outlet of the holding furnace is opened, and the aluminum liquid flows through the heating channel into a conventional rotor-type online degassing device and a two-stage filtration device. After online degassing and two-stage filtration, the temperature is naturally cooled to 718℃, and 0.15 wt.% is added through the wire feeder. Al-5Ti-0.8B-0.2C intermediate alloy wire is smoothly introduced into the crystallizer of a hot-top semi-continuous casting machine through a distribution channel. It is cast into a rod under the process parameters of casting speed 100mm / min and cooling water temperature 25℃. The rod is first held at 300℃ for 2 hours, and then heated to 420℃ and held for another 2 hours for two-stage homogenization annealing. After air cooling to room temperature, the high conductivity aluminum material for new energy vehicles is obtained. Example 2

[0028] A method for preparing a high conductivity aluminum material for new energy vehicles includes the following steps: S1. Prepare 1070 aluminum ingots and clean waste materials according to the ratio of clean waste materials not exceeding 30% of the total feed amount. Select 1070 industrial pure aluminum ingots and clean waste materials with aluminum content ≥99.7wt.%, Fe≤0.15wt.%, and Si≤0.08wt.%. The waste materials are dried in a drying kiln at 250℃ for more than 2 hours to remove moisture and oil. The pure aluminum is heated to 752℃ to melt it. Perform pre-analysis of the spectrum before the furnace. Take the aluminum liquid in the furnace and use a direct reading spectrometer to quickly determine the actual mass percentage of Ti, V, Cr, and Mn elements in the melt. Calculate the molar ratio of boron to Ti+V+Cr+Mn elements as 1.2:1. According to the pre-analysis results, add Al-3B with a boron content of 3wt.% to make the total amount of boron elements actually fed into the furnace 0.024wt.%. Stir thoroughly and keep it at 735℃ for 70 minutes. S2. Under the condition of maintaining 732℃, the boron-containing precipitate, accounting for 5-8% of the total mass of the molten aluminum, is extracted and discarded using a siphon method. The upper clear liquid is transferred to a preheated holding furnace and held at 725℃ for 30 minutes. The scum is skimmed off periodically, and the upper clear liquid is sampled for composition analysis to confirm that the residual boron content is ≤0.003wt.%. The aluminum outlet of the holding furnace is opened, and the molten aluminum flows through the heating channel into a conventional rotor-type online degassing device and a two-stage filtration device. After online degassing and two-stage filtration, the temperature is naturally cooled to 715℃, and 0.18wt.% is added through the wire feeder. Al-5Ti-0.8B-0.2C intermediate alloy wire is smoothly introduced into the crystallizer of a hot-top semi-continuous casting machine through a distribution channel. It is cast into a rod under the process parameters of casting speed 100mm / min and cooling water temperature 25℃. The rod is first held at 300℃ for 2 hours, and then heated to 420℃ and held for another 2 hours for two-stage homogenization annealing. After air cooling to room temperature, the high conductivity aluminum material for new energy vehicles is obtained. Example 3

[0029] A method for preparing a high conductivity aluminum material for new energy vehicles includes the following steps: S1. Prepare 1070 aluminum ingots and clean waste materials according to the ratio of clean waste materials not exceeding 30% of the total feed amount. Select 1070 industrial pure aluminum ingots and clean waste materials with aluminum content ≥99.7wt.%, Fe≤0.15wt.%, and Si≤0.08wt.%. The waste materials are dried in a drying kiln at 250℃ for more than 2 hours to remove moisture and oil. The pure aluminum is heated to 754℃ to melt it. Perform pre-analysis of the spectrum before the furnace. Take the aluminum liquid in the furnace and use a direct reading spectrometer to quickly determine the actual mass percentage of Ti, V, Cr, and Mn elements in the melt. Calculate the molar ratio of boron to Ti+V+Cr+Mn elements as 1.3:1. According to the pre-analysis results, add Al-3B with a boron content of 3wt.% to make the total amount of boron elements actually fed into the furnace 0.016wt.%. Stir thoroughly and keep it at 730℃ for 65 minutes. S2. Under the condition of maintaining 730℃, the boron-containing precipitate, accounting for 5-8% of the total mass of the molten aluminum, is extracted and discarded using a siphon method. The upper clear liquid is transferred to a preheated holding furnace and held at 720℃ for 30 minutes. The scum is skimmed off periodically, and the upper clear liquid is sampled for composition analysis to confirm that the residual boron content is ≤0.003wt.%. The aluminum outlet of the holding furnace is opened, and the molten aluminum flows through the heating channel into a conventional rotor-type online degassing device and a two-stage filtration device. After online degassing and two-stage filtration, the temperature is naturally cooled to 718℃, and 0.18wt.% is added through the wire feeder. Al-5Ti-0.8B-0.2C intermediate alloy wire is smoothly introduced into the crystallizer of a hot-top semi-continuous casting machine through a distribution channel. It is cast into a rod under the process parameters of casting speed 100mm / min and cooling water temperature 25℃. The rod is first held at 300℃ for 2 hours, and then heated to 420℃ and held for another 2 hours for two-stage homogenization annealing. After air cooling to room temperature, the high conductivity aluminum material for new energy vehicles is obtained.

[0030] Comparative Example 1 A method for preparing aluminum materials for new energy vehicles, the steps not specifically described are basically the same as in Example 1, the main difference being: In this comparative example, the grain refiner and pure aluminum were added together.

[0031] Comparative Example 2 A method for preparing aluminum materials for new energy vehicles, the steps not specifically described are basically the same as in Example 1, the main difference being: This comparative example does not perform pre-furnace spectral analysis, but directly adds Al-3B to make the theoretical boron content account for 0.02 wt.% of the total melt weight.

[0032] Comparative Example 3 A method for preparing aluminum materials for new energy vehicles, the steps not specifically described are basically the same as in Example 1, the main difference being: This comparative example does not use the siphon method for bottom slag removal.

[0033] Comparative Example 4 A method for preparing aluminum materials for new energy vehicles, the steps not specifically described are basically the same as in Example 1, the main difference being: This comparative example does not undergo two-stage homogenization annealing.

[0034] Comparative Example 5 A method for preparing aluminum materials for new energy vehicles includes the following steps: S1. Prepare 1070 aluminum ingots and clean waste materials according to the proportion of clean waste materials not exceeding 30% of the total feed amount. Select 1070 industrial pure aluminum ingots and clean waste materials with aluminum content ≥99.7wt.%, Fe≤0.15wt.%, and Si≤0.08wt.%. The waste materials are dried in a drying kiln at 250℃ for more than 2 hours to remove moisture and oil. Heat the pure aluminum and 0.15wt.% Al-5Ti-0.8B-0.2C intermediate alloy wire to 754℃ to melt them. Add Al-3B with a boron content of 3wt.% to make the theoretical total boron element in the furnace 0.021%. Stir thoroughly and keep at 732℃ for 65 minutes. S2. Under the condition of maintaining 730℃, the upper clear liquid is transferred to a preheated holding furnace and held at 722℃ for 30 minutes. The scum is skimmed off periodically, and the upper clear liquid is sampled for composition analysis to confirm that the boron element residue is ≤0.003wt.%. The aluminum outlet of the holding furnace is opened, and the aluminum liquid enters the conventional rotor-type online degassing device and the double-stage filtration device through the heating channel. After online degassing and double-stage filtration, it is naturally cooled to 718℃ and smoothly introduced into the crystallizer of the hot-top type horizontal semi-continuous casting machine through the distribution channel. It is cast into a casting rod under the process parameters of casting speed 100mm / min and cooling water temperature 25℃. The rod is processed into a 12mm×12mm×90mm sample. Lubricant is applied to the sample surface, and four passes of equal channel deformation are performed. The inner angle Φ of the mold is 90°. The sample is not rotated in each deformation pass. The deformation speed is 12mm / min, which yields the high conductivity aluminum material for new energy vehicles.

[0035] The main difference between this comparative example and Example 1 is that the casting rod is post-processed using ECAP.

[0036] Microstructural analysis was performed on Examples 1 and 3. In Example 1, a metallographic sample was taken from the tail end of the cast rod, and in Example 3, a metallographic sample was taken from the steady-state section in the middle of the cast rod. The metallographic images are shown below. Figure 1 , Figure 2 As shown.

[0037] Figure 1 The image shows the metallographic diagram of the high conductivity aluminum material for new energy vehicles prepared in Example 1 of this invention. As can be seen from the image, the average grain size is 105-110 μm, the structure is columnar crystal, the particles within the grains are uniformly dispersed, and the grain boundaries contain iron-containing compounds. No significant abnormalities were observed.

[0038] Figure 2The image shows the metallographic diagram of the high conductivity aluminum material for new energy vehicles prepared in Example 3 of this invention. As can be seen from the figure, the average grain size is 50-70 μm, which is significantly better than conventional refining treatment and continuous casting process. The structure is columnar crystal, with good structure and no defects such as feathery crystals, cracks, pores, shrinkage porosity, etc. The particles in the grain are uniformly dispersed, and the grain boundaries are distributed with iron phase compounds, with no significant abnormalities observed.

[0039] Performance tests were conducted on Examples 1-3 and Comparative Examples 1-5, and the specific test methods are shown below: electrical conductivity The tests were conducted according to GB / T 12966-2022 "Eddy Current Test Method for Conductivity of Aluminum and Aluminum Alloys". Samples with a thickness of not less than 10 mm were cut from the cast rods prepared in the various examples and comparative examples. The sample surface was polished to remove oxide scale, ensuring a smooth, clean surface free of scratches and oil stains. An eddy current conductivity meter with a frequency of 60 kHz ± 1% and an instrument resolution of 0.1% IACS was used for testing. The instrument was calibrated using a standard conductivity calibration block before testing, with a calibration cycle not exceeding 12 months. In a constant temperature environment of 20℃ ± 2℃, the eddy current probe was vertically attached to the sample surface. Three different locations were selected for measurement on each sample, and the average value was taken as the conductivity value of that sample. The results are expressed as %IACS (International Standard for Annealed Copper).

[0040] hardness Brinell hardness testing was conducted according to GB / T 231.1-2018 "Metallic Materials - Brinell Hardness Testing - Part 1: Test Method". Samples with a thickness of not less than 15 mm were cut from the cast rods prepared in the various examples and comparative examples. The test surface was ground and polished, with a surface roughness Ra not exceeding 1.6 μm. A 10 mm diameter cemented carbide ball indenter was used, with a test force of 3000 kgf and a holding time of 15 s. After removing the test force, the indentation diameter was measured using a reading microscope with a measurement accuracy of not less than 0.01 mm. The indentation diameter was calculated using the formula HBW = 0.102 × 2F / (πD·(D-√(D)). 2 -d 2 Calculate the Brinell hardness value, where F is the test force (N), D is the diameter of the ball indenter (mm), and d is the average diameter of the indentation (mm). Three indentations are measured at different locations for each type of specimen, and the average value is taken.

[0041] Tensile strength and elongation Tensile strength and elongation were tested according to GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Tests at room temperature". Tensile specimens were cut longitudinally from the cast bars prepared in the various examples and comparative examples. The gauge length diameter was 10 mm, the gauge length was 50 mm (i.e., 5 times the diameter of the specimen), the parallel length of the specimen was not less than 65 mm, and the length of the threaded or stepped clamping ends was not less than 30 mm at each end. Tensile tests were performed using a universal testing machine until the specimen fractured. The yield strength ReH was recorded as the tensile strength (MPa), calculated using the formula A = (L... u The elongation rate is calculated as (-L0) / L0×100%, where L0 is the original gauge length, and L... u This represents the gauge length after fracture. Three specimens of each type were tested, and the average value was taken.

[0042] Heat resistance Following the general principles of GB / T 33370-2016 "Determination of Softening Temperature of Copper and Copper Alloys" and combining common methods for testing the heat resistance of aluminum alloys, heat resistance performance was tested. Tensile specimens were cut from the cast rods prepared in the various examples and comparative examples, placed in an air-circulating furnace, and held at 280℃±2℃ for 1 hour before being air-cooled to room temperature. The tensile strength of the specimens after holding was tested according to the tensile test method of GB / T 228.1-2021, and calculated using the formula η=R m1 / R m0 ×100% Calculate the strength retention rate, where R m1 R is the tensile strength after heat preservation at 280℃ for 1 hour. m0 The original tensile strength of the uninsulated specimens is given, and the results are expressed as a percentage. Three specimens of each type were tested, and the average value was taken.

[0043] The specific performance test results of Examples 1-3 and Comparative Examples 1-5 are shown in the table below: Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-5 As shown in Table 1, the conductivity of the high-conductivity aluminum materials for new energy vehicles prepared in Examples 1-3 of this invention is ≥64% IACS. Among them, the total amount of boron in Example 3 is 0.016%, which is the lowest among the three examples, and the conductivity is the highest, reaching 65.37% IACS. This indicates that, under the premise of ensuring sufficient boronization reaction, a low amount of boron addition is more conducive to reducing the negative impact of residual boron on conductivity. The hardness reaches about 35 HBW, the tensile strength is not less than 110 MPa, and the elongation is maintained at about 44%, which balances strength and plasticity. The mechanical properties are balanced and excellent. After heat preservation at 280℃ for 1 hour, the strength retention rate is above 91%, showing excellent heat resistance stability. An excellent balance is achieved between conductivity, strength, plasticity and heat resistance. All performance indicators meet the reliability requirements of high-end conductive materials in the field of new energy vehicles.

[0044] In Comparative Example 1, the grain refiner was added together with pure aluminum. The grain refiner particles remained in the melt for a long time and coarsened due to high-temperature agglomeration, which reduced the refinement efficiency. Furthermore, the particles were easily intercepted and lost by the filtration device in the subsequent two-stage filtration, resulting in a reduction in the effective grain refiner entering the ingot. The grain refinement effect was further reduced, and the conductivity dropped to 63.51% IACS. At the same time, the tensile strength dropped to 106.8 MPa, the elongation dropped to 39.8%, and the Brinell hardness dropped to 33.4 HBW. After grain coarsening, the total grain boundary area decreased, the grain boundary pinning effect at high temperatures weakened, and the heat resistance stability decreased. The strength retention rate was 89.9%, and the overall performance was poor.

[0045] Comparative Example 2 did not undergo pre-furnace spectral analysis and directly added 0.02 wt.% Al-3B. The actual content of impurity elements such as Ti, V, Cr, and Mn in the melt could not be determined. If the impurity content was high and the amount of B added was insufficient, the boration reaction would be incomplete, and the impurity elements would still exist in large quantities in solid solution, severely scattering electrons. If the impurity content was low and the amount of B added was excessive, residual B would remain in solid solution in the aluminum matrix, similarly impairing conductivity. Neither scenario could achieve optimal conductivity, resulting in a conductivity drop to 62.02% IACS, the lowest among all samples. Inappropriate B addition led to unstable grain refinement, and the lattice distortion caused by residual B solid solution had an uneven hindering effect on dislocation movement, resulting in a decrease in mechanical properties as well. The tensile strength was 108.1 MPa and the elongation was 40.5%.

[0046] Comparative Example 3 did not use the siphon method for bottom slag removal. The boride precipitate generated after the borylation treatment was resuspended or underwent secondary melting during the subsequent aluminum liquid transfer and casting process. This caused the impurity elements that had changed from the solid solution state to the precipitated state to re-enter the aluminum matrix, offsetting the purification effect of the borylation treatment. As a result, the conductivity dropped to 62.81% IACS, which was 2.21 percentage points lower than that of Example 1, and second only to Comparative Example 2 among all comparative examples.

[0047] Comparative Example 4, without two-stage homogenization annealing, exhibited severe intragranular segregation and supersaturated solid solution elements in its as-cast microstructure. These elements existed in large quantities in the aluminum matrix in solid solution, resulting in a decrease in conductivity to 63.48% IACS. The non-equilibrium eutectic phase and coarse grains in the as-cast microstructure weakened the strengthening effect. The supersaturated solid solution in the unannealed sample exacerbated grain boundary weakening at high temperatures, making grain boundary sliding more likely and leading to rapid strength decay. Consequently, mechanical properties and heat resistance decreased significantly, with a strength retention rate of only 89.4%, the lowest among all samples.

[0048] Comparative Example 5, after post-processing the cast rod using ECAP, achieved a tensile strength of 162.5 MPa, the highest among all samples, thanks to the fine-grained strengthening and dislocation strengthening brought about by intense plastic deformation. However, the high dislocation density and ultrafine-grained structure severely limited the plastic deformation capacity, causing the elongation to plummet to 12.5%, less than one-third of that of Example 1. Furthermore, the high-density dislocations introduced by ECAP recovered at high temperatures, leading to a decrease in dislocation density and strength degradation, with a strength retention rate of 89.6%, slightly lower than the level of the Example 1. This comparative example demonstrates that while ECAP can significantly improve strength, it comes at the cost of conductivity and plasticity, offering no advantage in high-temperature heat resistance. It also exhibits poor room-temperature formability, making subsequent processing difficult and unsuitable for manufacturing high-performance wires and connectors for new energy vehicles.

[0049] In summary, this invention utilizes pre-furnace spectral analysis for dynamic boron addition, precisely matching the boron addition amount with the impurity content. This ensures that Ti, V, Cr, and Mn are fully converted into boride precipitates while avoiding excessive boron residue, providing precise dosage guidance for the boration process. A siphon is used to actively extract and discard the boride precipitate layer from the furnace bottom, physically removing the products of the boration reaction and preventing secondary melting or resuspension of the boride in subsequent processes. Regular skimming of scum further facilitates purification and removal of boration reaction products. Online degassing and dual-stage filtration provide a high-purity melt environment for delayed grain refinement. The grain refiner is fed after the dual-stage filtration device and before the distribution trough. At this point, the aluminum melt has naturally cooled to 710-720℃, and the melt purity is optimal, which is conducive to the uniform dispersion of refined particles and maximizes nucleation efficiency. The temperature is lower than that of conventional grain refinement addition. Temperature increases the supercooling of the melt, causing the grain refiner particles to precipitate in a finer and more dispersed form, significantly improving nucleation efficiency. Only a low dose is needed to achieve a uniform equiaxed grain structure of 50-70μm, avoiding the negative impact of excessive Ti and B on conductivity in high-dose refiners. This provides a uniform and fine equiaxed grain structure for the ingot. The two-stage homogenization annealing releases the best conductivity and mechanical properties for the final product, enabling the stable production of high-conductivity aluminum materials for new energy vehicles with a conductivity of over 64% IACS. This significantly improves the material's conductivity and achieves an excellent balance between conductivity, strength, plasticity, and heat resistance. The production process is complete and highly controllable, with key process parameters that can be precisely controlled, ensuring batch stability and consistency of product performance. All performance indicators meet the reliability requirements of high-end conductive materials in the new energy vehicle field.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high conductivity aluminum material for new energy vehicles, characterized in that, Includes the following steps: S1. Heat pure aluminum to 750-760℃ to melt it. Perform pre-furnace spectral analysis to determine the actual mass percentage of Ti, V, Cr, and Mn elements in the melt. Based on the pre-analysis results, add Al-3B to make the total mass percentage of boron elements actually entering the furnace 0.015-0.025 wt.%. Stir thoroughly and keep at 730-735℃ for 60-90 minutes. S2. The boron-containing precipitate at the bottom of the furnace is extracted and discarded by siphon method. The clear liquid at the top is kept at 715-725℃ for 30 minutes. The scum is skimmed off periodically, the gas is degassed online, filtered in two stages, and cooled naturally to 710-720℃. A grain refiner is added, and the mixture is semi-continuously cast and then homogenized in two stages to obtain the high conductivity aluminum material for new energy vehicles.

2. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The pure aluminum mentioned in S1 is 1070 industrial pure aluminum, with an aluminum content ≥99.7wt.%, Fe≤0.15wt.%, and Si≤0.08wt.%.

3. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The boron content in Al-3B described in S1 is 2.5-3.5 wt.%.

4. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The amount of Al-3B added in S1 is calculated based on the molar ratio of boron to Ti+V+Cr+Mn elements as (1.2-1.5):

1.

5. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The boron-containing precipitate in S2 accounts for 5-8 wt.% of the total mass of the molten aluminum.

6. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The operating temperature for extracting and discarding boron-containing precipitates from the bottom of the furnace using the siphon method, as described in S2, is controlled at 720-735℃.

7. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: After periodically skimming off the scum as described in S2, the process also includes taking a sample of the supernatant for composition analysis to confirm that the residual boron content is ≤0.003wt.%.

8. The method for preparing a high conductivity aluminum material for new energy vehicles according to claim 1, characterized in that: The grain refiner mentioned in S2 is Al-5Ti-0.8B-0.2C, and the addition amount is 0.10-0.18 wt.%.

9. A high conductivity aluminum material for new energy vehicles, characterized in that: Prepared by the preparation method according to any one of claims 1-8.

10. A high conductivity aluminum material for new energy vehicles according to claim 9, characterized in that, By weight percentage, it includes: Fe≤0.15wt.%, Si≤0.08wt.%, Cr+Mn+V+Ti≤0.01wt.%, Al≥99.75wt.%.

Citation Information

Patent Citations

  • Method for preparing boron-modified commercially pure aluminum with high strength and conductivity

    CN102978481B